Identificación molecular y perfil de sensibilidad antifúngica de Candida albicans y Candida dubliniensis aisladas de pacientes ambulatorios y hospitalizados - Duré, Carolina; Samudio, Margarita; Fariña, Norma; Abente, Sonia; Pereira, Alicia; Guillén, Rosa; Aguilar, Gustavo; Gayoso, Belén; Nuñez, Heriberto; Almirón, Desiré; Taboada, Aurelia (Medicina Clínica y Social, 2024)
Introduction: C. albicans together with C. dubliniensis and C. Africana, form the Candida albicans Complex. These species are closely related to each other, making differentiation by conventional methods difficult. Objectives: To differentiate Candida albicans and Candida dubliniensis by molecular method in isolates from outpatients and hospitalized patients from Central, Paraguay and to know their susceptibility profile. Methods: Yeasts isolated from respiratory materials, oral cavity, purulent secretions, blood, urine and others were included. An end-point duplex PCR was performed on the isolates that developed greenish coloration in chromogenic medium (CONDA®, Spain). DNA was extracted using the Wizard® Genomic DNA Kit (Promega, USA) with some modifications. Antifungal susceptibility was determined by VITEK® 2 to a subgroup of isolates. Results: Of 1065 isolates, 838 (78,7 %) were C. albicans and 3 (0,3 %) C. dubliniensis, the latter coming from the oral cavity; the remaining 224 were negative for both species. 94,4 % of 503 C. albicans isolates were susceptible to fluconazole, 97,6 % to voriconazole, 99,4 % to amphotericin B, 100 % to caspofungin and micafungin. The three isolates of C. dubliniensis presented MICs of ? 0,5 µg/mL against fluconazole, ? 0,12 µg/mL against voriconazole and ? 0,25 µg/mL against amphotericin B. Conclusions: The frequency of C. dubliniensis is low compared to other studies that report values ??of 1,5 to 32 %. These isolates did not exhibit signs of resistance. C. albicans exhibited good susceptibility to antifungals tested.